2021
DOI: 10.21037/sci-2021-008
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of leukocyte recovery predict infectious complications after CD19 CAR-T cell therapy in a real-world setting

Abstract: Background: Adoptive immunotherapy using CD19-targeted Chimeric antigen receptor T cells (CAR-T) has revolutionized the treatment of relapsed/refractory diffuse large B-cell lymphoma (DLBCL). Data is limited on the propensity of infections and lymphohematopoietic reconstitution after Day 30 (D30) following CAR-T cell therapy. In this study, we evaluated the prevalence and nature of infectious complications in an expanded cohort of DLBCL patients treated with CD19 CAR-T therapy and its association with the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Neutropenia and lymphocytopenia are fairly universal before and after infusion. The duration of severe neutropenia can also be prolonged in 16% of cases, maintaining a high risk of infection over time [ 143 ]. In a retrospective study including 19 patients who received CD19 CAR-T cells, the absolute count of neutrophils and monocytes compared to the absolute lymphocyte count predicted infectious complications [ 144 ].…”
Section: Adoptive T/nk Cell Therapymentioning
confidence: 99%
“…Neutropenia and lymphocytopenia are fairly universal before and after infusion. The duration of severe neutropenia can also be prolonged in 16% of cases, maintaining a high risk of infection over time [ 143 ]. In a retrospective study including 19 patients who received CD19 CAR-T cells, the absolute count of neutrophils and monocytes compared to the absolute lymphocyte count predicted infectious complications [ 144 ].…”
Section: Adoptive T/nk Cell Therapymentioning
confidence: 99%
“…Grade 3 cytopenias developing >30 days after CAR T-cell infusion are defined as prolonged haematological toxicity, 107,109 occur in about 10%-20% of cases, and may present in two waves with a biphasic temporal course. 107,[110][111][112][113] Haematological toxicity is the most common adverse event after CAR T-cell therapy, with a cumulative 1-year incidence of 58% in the real-world setting. 110 In the ZUMA-1 study, neutropenia, anaemia and thrombocytopenia were observed in 78%, 43% and 38% of patients respectively.…”
Section: Commentsmentioning
confidence: 99%
“…35,54,110,114,[116][117][118][119] Risk factors for severe infections include severe CRS/ICANS, cytopenia prior to lymphodepletion, and prior allo-HSCT. 107,[109][110][111][112][113]115 Moreover, the severity of cytopenias correlates with the degree of CRS. 107 Other prognostic risk factors for infections after CAR T-cell therapy include age and immune reconstitution.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has proposed certain patterns of leukocyte recovery as potential novel predictors of infection in CAR T recipients. 7 There are recommendations to screen, monitor, and prevent infectious diseases in recipients of this therapy. [8][9][10] It is important to highlight the risk of reactivation of infections that could have remained latent under initial chemotherapy; in some cases, prophylaxis is recommended from the beginning of CAR T, or after close monitoring and detection of an increased risk in initially low-risk patients (as per hepatitis B infection and entecavir therapy, in patients who have antibodies against the surface of hepatitis B-anti-HBs + ), 10 but guidelines vary according to authors.…”
mentioning
confidence: 99%